Somatotype of the Tarung Derajat martial arts athletes in the fighter category - Samodra, Y. Touvan Juni; Gustian, Uray; Seli, Sesilia; Riyanti , Dwi; Suryadi, Didi; Fauziah, Ella; Mashud (Journal Sport Area, 2023)
Somatotype is a parameter used to determine criteria based on body type. However, not many have taken somatotype measurements when selecting prospective athletes. The purpose of this study is to examine the somatotype of fighters in Tarung Derajat Martial Arts. In this study, tests and measurements of somatotype were carried out using manual anthropometric measurements, including height, weight, skinfold measurements at five points (biceps, triceps, suprailliaca, subscapula, and calf), arm circumference, calf circumference, and measurement of the width of the humerus bone and femur. The purposive sampling technique is used in determining the sample. In this study, 15 Tarung Derajat martial arts athletes, consisting of seven men and eight women, were sampled. The results of this study showed that 7 athletes had a mesomorph endomorph somatotype with a percentage of 46%, 1 athlete had an endomorph somatotype with a 7% percentage, 6 central athletes had a percentage of 40%, and 1 athlete had an ectomorph endomorph somatotype with a percentage of 7%. Finally, the dominant body type in Tarung Derajat Fighter athletes is mesomorph endomorph (46%), followed by central (40%). This study's data provide physical characteristics of degree fighters, which can be used to establish a reference for systematic sports medicine research.